Effect of cervical headgear wear on dynamic measurement of head position - (:unkn) unknown (OXFORD UNIV PRESS, 2005)
The aim of this study was to identify the effect of cervical headgear (CHG) wear on dynamic measurement of head posture during walking. Six male and 10 female patients (mean age, 11.9 +/- 1.9 years) who were receiving CHG therapy for correction of a Class II molar relationship as part of their orthodontic treatment were included in this study. Dynamic head posture measurements were recorded using an inclinometer and data logger apparatus during a walking session of 5 minutes. This procedure was repeated before (T1) and after (T2) insertion of CHG. The T1 and T2 measurements were repeated twice at 30-minute intervals. The mean dynamic head posture was calculated for each subject using the collected data. The means of these measurements were statistically compared using a paired t-test. Of the 16 subjects, 14 showed a cranial flexion with CHG wear in relation to T1 (1.4 to 8.9 degrees). The other two subjects showed a cranial extension of -1.6 and -3.8 degrees. The mean values at T1, T2 and T1-T2 were 1.4, -1.8, and 3.1 degrees, respectively, which indicated a mean cranial flexion at T2 in relation to T1. According to the paired sample t-test, there were statistically significant differences between the two measurements of dynamic head posture recorded before and after CHG insertion (P < 0.001). CHG wear causes a significant cranial flexion which may be responsible for its effects on the mandible.
Keywords: CLASS-II TREATMENT; CRANIOFACIAL MORPHOLOGY; CRANIOCERVICAL POSTURE; INCLINOMETER; MALOCCLUSION; TRACTION; RETRACT; MAXILLA; FORCES; GROWTH